Optimum design of Tension Steel Members L-Section by using Artificial Neural Networks - الوفائي رنيم (Latakia University Journal -Engineering Sciences Series, 2021)
This search this will study how to design steel tension members L-section by using Artificial Neural Networks , where Artificial Neural Networks technology was used in one of the structural design cases , which is design the L-shaped steel sections that are subject to tension in accordance with the European code and to give the minimum cost of the member (the most efficient). In our search 132 samples were taken for use in Artificial Neural Network design , the network has been trained on them , tasted and ensuring their effectiveness in finding the optimal format . The designed Network model was able to predict the most cost effective design variables namely width (b) and thickness (t) of the required section , with precision in design to meet all limitations. A comparison of the results showed the effectiveness of this technique with the saving in the required section cost .